A new Gastropanel quick test for non-invasive diagnosys in dyspeptic patients. The first experience in primary care setting in North East Italy - Di Mario, Francesco; Franceschi, Marilisa; Rodriguez Castro, Kryssia Isabel; Franzoni, Lorella; Panizza, Cecilia; Vano, Roberto; Gombac, Francesca; Tursi, Antonio; Brandimarte, Giovanni; Crafa, Pellegrino (Acta Biomedica Atenei Parmensis, 2025)
Background: Gastropanel is a non-invasive serological test based on Pepsinogens, Gastrin 17, IgG against Hp. Aim of the study: To assess the clinical usefulness of a new quick gastropanel test in a sample of dyspeptic patients in primary care setting.Methods: The GastroPanel® quick test (Biohit Finland), is a rapid lateral flow immunochromatographic POCT test. The results could be available in fifteen minutes.Patient's Population: One hundred and eighty-eight (76 M, 112 F) dyspeptic patients were investigated by using  serum pepsinogens, gastrin 17 and IgG against (quick Gastropanel Test).Results: Patients were singled out as follows: 1) Functional Dyspepsia (72 pts); 2) GERD (40 pts) 3) GERD under PPIs (37 pts), 4) Non-Atrophic Gastritis Hp + (29 pts), 5 Autoimmune Atrophic Gastritis (6 pts), 6) Multifocal Atrophicc Gastritis (4 pts). PGI: the greatest increase in patients on PPIs therapy (148.1 mg/L; p